Effectiveness of Tocilizumab with and without Dexamethasone in Patients with Severe COVID-19: A Retrospective Study - Zarębska-Michaluk D; Jaroszewicz J; Rogalska M; Martonik D; Pabjan P; Berkan-Kawińska A; Bolewska B; Oczko-Grzesik B; Kozielewicz D; Tudrujek-Zdunek M; Kowalska J; Moniuszko-Malinowska A; et al. (Dove Medical Press, 2021)
Dorota Zarębska-Michaluk,1 Jerzy Jaroszewicz,2 Magdalena Rogalska,3 Diana Martonik,3 Paweł Pabjan,1 Aleksandra Berkan-Kawińska,4 Beata Bolewska,5 Barbara Oczko-Grzesik,2 Dorota Kozielewicz,6 Magdalena Tudrujek-Zdunek,7 Justyna Kowalska,8 Anna Moniuszko-Malinowska,9 Krzysztof Kłos,10 Marta Rorat,11,12 Piotr Leszczyński,13,14 Anna Piekarska,4 Joanna Polańska,15 Robert Flisiak3 1Department of Infectious Diseases, Jan Kochanowski University, Kielce, 25-369, Poland; 2Department of Infectious Diseases and Hepatology, Medical University of Silesia, Katowice, 40-055, Poland; 3Department of Infectious Diseases and Hepatology, Medical University of Białystok, Białystok, 15-089, Poland; 4Department of Infectious Diseases and Hepatology, Medical University of Łódź, Łódź, 90-549, Poland; 5Department of Infectious Diseases, University of Medical Sciences, Poznań, 61-701, Poland; 6Department of Infectious Diseases and Hepatology, Faculty of Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University, Toruń, 87-100, Poland; 7Department of Infectious Diseases and Hepatology, Medical University of Lublin, Lublin, 20-059, Poland; 8Department of Adults' Infectious Diseases, Medical University of Warsaw, Warsaw, 02-091, Poland; 9Department of Infectious Diseases and Neuroinfections, Medical University of Białystok, Białystok, 15-089, Poland; 10Department of Infectious Diseases and Allergology, Military Institute of Medicine, Warsaw, 04-141, Poland; 11Department of Forensic Medicine, Wrocław Medical University, Wrocław, 50-367, Poland; 12First Infectious Diseases Ward, Gromkowski Regional Specialist Hospital in Wrocław, Wrocław, 51-149, Poland; 13Department of Rheumatology, Rehabilitation and Internal Medicine, Poznan University of Medical Sciences, Poznań, 61-701, Poland; 14Department of Rheumatology and Osteoporosis, Szpital im. J. Strusia w Poznaniu, Poznań, 61-285, Poland; 15Silesian University of Technology, Gliwice, 44-100, PolandCorrespondence: Dorota Zarębska-MichalukDepartment of Infectious Diseases, Jan Kochanowski University in Kielce, Ul. Radiowa 7, Kielce, 25-317, PolandTel +48 662441465Fax +48 41 3682262Email dorota1010@tlen.plPurpose: The pathogenesis of coronavirus disease 2019 (COVID-19) is complicated, and in addition to antiviral therapy and combating coagulopathy, treatment should also include inhibition of the proinflammatory cytokines overproduction. The purpose of this study is to compare the effectiveness of tocilizumab (TCZ) and dexamethasone (DEX) administered alone or in combination in patients with severe COVID-19.Patients and Methods: Patients were selected from the SARSTer database, containing 3330 individuals with COVID-19 treated between 1 March 2020 and 10 March 2021. The current study included adult patients with baseline oxygen saturation (SpO2) ≤ 90%, requiring regular or non-invasive high-flow oxygen supplementation.Results: Among included 460 patients, 59 were treated with TCZ, 125 with TCZ and DEX, 169 with DEX, and 107 did not receive TCZ nor DEX. The groups were balanced regarding demographics, coexisting diseases, baseline SpO2, and comedications with remdesivir or low-molecular-weight heparin. The death rate of 6.8% was significantly lower in patients receiving TCZ alone than each arm (19.6%- 23.1%), particularly in patients with interleukin-6 concentration exceeding 100pg/mL (5% vs 22.9%- 51.7%, respectively). Analysis of clinical improvement demonstrated doubled, significantly higher rate after 21 and 28 days in patients treated with TCZ alone (60% and 75%, respectively) compared to DEX (27.6% and 37.9%, respectively). The need for mechanical ventilation was similar in all arms.Conclusion: In patients with severe course of COVID-19, particularly those developing cytokine storm, administration of TCZ provides a significantly better effect than DEX regarding survival, clinical improvement, and hospital discharge rate. The combination of TCZ and DEX does not improve therapy effectiveness in patients with severe COVID-19 compared to the administration of TCZ alone.Keywords: SARS-CoV-2, COVID-19, tocilizumab, dexamethasone, cytokine storm